Development of a standardized histopathology scoring system for intervertebral disc degeneration and regeneration in rabbit models‐An initiative of the ORSspine section. Issue 2 (3rd June 2021) - Gullbrand, Sarah E.; Ashinsky, Beth G.; Lai, Alon; Gansau, Jennifer; Crowley, James; Cunha, Carla; Engiles, Julie B.; Fusellier, Marion; Muehleman, Carol; Pelletier, Matthew; Presciutti, Steven; Schol, Jordy; et al.
Abstract: Background: The rabbit lumbar spine is a commonly utilized model for studying intervertebral disc degeneration and for the pre‐clinical evaluation of regenerative therapies. Histopathology is the foundation for which alterations to disc morphology and cellularity with degeneration, or following repair or treatment are assessed. Despite this, no standardized histology grading scale has yet been established for the spine field for any of the frequently utilized animal models. Aims: The purpose of this study was to establish a new standardized scoring system to assess disc degeneration and regeneration in the rabbit model. Materials and Methods: The scoring system was formulated following a review of the literature and a survey of spine researchers. Validation of the scoring system was carried out using images provided by 4 independent laboratories, which were graded by 12 independent graders of varying experience levels. Reliability testing was performed via the computation of intra‐class correlation coefficients (ICC) for each category and the total score. The scoring system was then further refined based on the results of the ICC analysis and discussions amongst the authors. Results: The final general scoring system involves scoring 7 features (nucleus pulposus shape, area, cellularity and matrix condensation, annulus fibrosus/nucleus pulposus border appearance, annulus fibrosus morphology, and endplate sclerosis/thickening) on a 0 (healthy) to 2 (severe degeneration) scale. ICCs demonstrated overall moderate to good agreement across graders. An addendum to the main scoring system is also included for use in studies evaluating regenerative therapeutics, which involves scoring cell cloning and morphology within the nucleus pulposus and inner annulus fibrosus. Discussion: Overall, this new scoring system provides an avenue to improve standardization, allow a more accurate comparison between labs and more robust evaluation of pathophysiology and regenerative treatments across the field. Conclusion: This study developed a histopathology scoring system for degeneration and regeneration in the rabbit model based on reported practice in the literature, a survey of spine researchers, and validation testing. Abstract : The rabbit lumbar spine is a commonly utilized model for studying intervertebral disc degeneration and for the pre‐clinical evaluation of regenerative therapies, and histopathology is the foundation for which alterations to disc morphology and cellularity with degeneration, or following repair or treatment are assessed. Despite this, no standardized histology grading scale has yet been established for the spine field for any of the frequently utilized animal models. Therefore, the purpose of this study was to establish a new standardized scoring system to assess disc degeneration and regeneration in the rabbit model.